Drilling study on CFRP/Al stack with different CFRP thickness using chip-breaking step drill bit. (24th March 2023) - Zhao, Meng; Wang, Fuji; Fu, Rao; Sun, Kai; Du, Changlin; Cui, Jiacheng
Abstract: Low-defect and high-accurate drilling is required for CFRP/Al stack assembly, while unexpected drill defects and inconsistency of hole diameter are often found in drilling different thickness stacks due to the lack of proper drilling process. First, a novel quantifying method for CFRP delamination and Al burr is proposed and a new quality indicator for hole diameter is developed to ensure the accuracy of evaluating the drilling quality. The stacks with different thicknesses were compared, and the subsequent effects of machining parameters on drilling quality were comprehensively investigated. Then considering the thrust force and drilling temperature together, the influence of thermal-mechanical interaction on the hole defects was elucidated for the first time in drilling different thick stacks. The results show that the thicker stacks increased the drilling temperature for the prolonged tool/material engagement time, and that the stiffness and strength of drilled material were reduced progressively as the higher temperature, leading to the lower thrust force. For the CFRP delamination, the thickness of the stack is found to be another significant factor determining the delamination damage, and a better CFRP quality can be obtained in drilling thicker stacks. The height of Al burr increased with the thickness increased due to the main effects of the increased temperature, but which decreased and then increased with the feed because the decreased drilling temperature played at low feed while decreased thrust force at a high feed played a decisive role separately. Smaller diameter deviation was found in drilling thicker stacks, for the reduced thrust force leading to the decreased deformation. Besides, the diameter deviation decreased with feed increased as the reduced temperature played a main role at low feed, while diameter deviation increased at a high feed because the thrust force increased. Finally, a multiple-objective optimization was modelled, and optimum drilling conditions for achieving desired hole quality were determined with the chip-breaking step drill bit for drilling different CFRP/Al stacks.